Secretion of the Phosphorylated Form of S100A9 from Neutrophils Is Essential for the Proinflammatory Functions of Extracellular S100A8/A9 - Schenten, Véronique; Plançon, Sébastien; Jung, Nicolas; Hann, Justine; Bueb, Jean-Luc; Bréchard, Sabrina; Tschirhart, Eric J.; Tolle, Fabrice (Frontiers in Immunology, 2018)
S100A8 and S100A9 are members of the S100 family of cytoplasmic EF-hand Ca2+-binding proteins and are abundantly expressed in the cytosol of neutrophils. In addition to their intracellular roles, S100A8/A9 can be secreted in the extracellular environment and are considered as alarmins able to amplify the inflammatory response. The intracellular activity of S100A8/A9 was shown to be regulated by S100A9 phosphorylation, but the importance of this phosphorylation on the extracellular activity of S100A8/A9 has not yet been extensively studied. Our work focuses on the impact of the phosphorylation state of secreted S100A9 on the pro-inflammatory function of neutrophils. In a first step, we characterized the secretion of S100A8/A9 in different stimulatory conditions and investigated the phosphorylation state of secreted S100A9. Our results on neutrophil-like differentiated HL-60 cells (dHL-60) and purified human neutrophils showed a time-dependent secretion of S100A8/A9 when induced by PMA and this secreted S100A9 was found in a phosphorylated form. Secondly, we evaluated the impact of this phosphorylation on pro-inflammatory cytokine expression and secretion in dHL-60 cells. Time course experiments with purified unphosphorylated or phosphorylated S100A8/A9 were performed and the expression and secretion levels of IL1α, IL1ß, IL6, TNFα, CCL2, CCL3, CCL4 and CXCL8 were measured by real-time PCR and cytometry bead array, respectively. Our results demonstrate that only the phosphorylated form of the complex induces pro-inflammatory cytokine expression and secretion. For the first time, we provide evidence that S100A8/PhosphoS100A9 is inducing cytokine secretion through TLR4 signaling.